2016
DOI: 10.1186/s40064-016-2972-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of electronic power transformer based on neuro-fuzzy controller

Abstract: In recent years, electronic power transformer (EPT), which is also called solid state transformer, has attracted great interest and has been used in place of the conventional power transformers. These transformers have many important functions as high unity power factor, low harmonic distortion, constant DC bus voltage, regulated output voltage and compensation capability. In this study, proposed EPT structure contains a three-phase pulse width modulation rectifier that converts 800 Vrms AC to 2000 V DC bus at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…Moreover, the rapid reduction of fossil fuel resources requires the search for alternative sources of energy to find a solution for future energy production. With the developing technology, the rising living standards and the increasing population, the requirement of electric energy is increasing day by day [1,3]. It is well-known that electricity is provided to consumers by passive transformers, transmission lines, and substations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the rapid reduction of fossil fuel resources requires the search for alternative sources of energy to find a solution for future energy production. With the developing technology, the rising living standards and the increasing population, the requirement of electric energy is increasing day by day [1,3]. It is well-known that electricity is provided to consumers by passive transformers, transmission lines, and substations.…”
Section: Introductionmentioning
confidence: 99%
“…New technological solutions are required to eliminate these problems. In addition, efforts to develop transformers with technological advances have been increasing rapidly in recent years [1,4,6,10]. New type transformers, which are considered as one of these technological developments, are called as solid state transformer (SST), intelligent universal transformer (IUT) or electronic power transformer (EPT) [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the SPC is suitable for dealing with a full range of unbalanced loads under the condition where the input-stage current stress increases. Nonlinear and intelligent controllers such as an internal model controller, a sliding mode controller, and a neurofuzzy controller are adopted in [18][19][20] to improve PET performance.…”
Section: Introductionmentioning
confidence: 99%